The analytical potentiality of three different liquid stationary phases in analysing rathylchlorosilanes by gas - liquid ehromatography - Baghdad Science Journal (مجلة بغداد للعلوم)
Organohalosilanes conslitute an important subject Ù¡Ù¦Ø› the chemistry oforganosilicon compoundØ›. Being starting materials and intermediates in the synthesis of a large number of various compounds so it is very important to get such materials in its highest purity ,but the separation of rathylchlorosilanes was still a big^oblem, duet^the great similarity in their physical and chemical properties, making its analysing verydifficult, ^or this reason tteir must be a good method o^e^r^iondealing^ththe^compounds, gas- liquid chromatography proved that it was the best, specially when (m- nitrotoluene) was used as a stationary liquid phase, it gave a complete separation and a good statistical results